The dynamics of the relationship between foreign exchange reserves and import demand function - Ibtisam Al Abri; Behnaz Saboori; Razan Al Humaidi (Cogent Economics & Finance, 2023)
This study empirically investigates the dynamics of the relationship between import demand and foreign exchange reserves for an oil-rich and high-income developing country, Oman. This study employs the Autoregressive Distributed Lag (ARDL) model to investigate the impact of real income, domestic prices, and foreign exchange reserves on aggregate and disaggregated import demand function. Results reveal that total imports are significantly affected by domestic prices only; whereas, demand for goods import is influenced by income. The level of foreign exchange reserves does not influence import demand function. These findings indicate that currency peg stabilization efforts, foreign asset leakages and varying sources of foreign currency could have weakened the link between foreign reserves and import levels. Considering domestic prices and income, competition and efficient production of local goods and services should be further encouraged, especially concerning ongoing issues like food security. Understanding import dynamics enhances robust import forecasts, international trade planning and policy formulation.
Keywords: E52; E58; F13; F31; 330; Auto-Regressive Distributed Lag (ARDL) model; Cointegration; Foreign exchange reserves; Import demand function; Oman